Electrical properties of highly conducting Sno2:Sb nanocrystals synthesized using a nonaqueous sol gel method - Conti, Tiago Góes; Chiquito, A. J.; Silva, Rafael Oliveira da; Longo, Elson [UNESP]; Leite, Edson Roberto (Wiley, 2010)
This work describes the synthesis of highly conducting antimony-doped tin oxide (ATO) nanocrystals prepared via a nonaqueous sol–gel route in the size range of 4–6 nm and provides insights into its electrical properties. The antimony composition was varied from 1 to 18 mol% and the lowest resistivity (4.0 × 10−4Ω·cm) was observed at room temperature in the SnO2:8.8 mol% Sb composition. The samples were evaluated by X-ray diffraction, high-resolution transmission electron microscopy, energy-dispersive X-ray spectroscopy, and scanning electron microscope, and resistivity measurements were taken in the four-probe mode in the temperature range of 13–300 K. The results show highly crystalline nanoparticles in a monodisperse colloidal system, dependence on the shape of ATO nanoparticles as a function of Sb distribution, low resistivity, and semiconductor–metal transition.